Grading and learning: variations and complexity from 19th century until nowadays - Nikolaienko, Olha (My University, 2024)
Grading is considered to be an integral part of various educational systems with an influence on students’ performances and learning outcomes. This thesis examines the multidimensional nature of grading from both historical and contemporary perspectives with an emphasis on interconnection between grades and learning. The comprehensive review of the grading practices from the late 19th century until current days reveals various researches in the field of education which attempt to find a solution to such issues as subjectivity in grading, standardisation, fairness and the ways grades influence student’s motivation. Yet, those areas remain open for further exploration since no unified solutions has been found. The findings of the study highlight the complexity of the grading issue and suggest that in order for the grades to be more fair and promote learning, multiple assessment tools should be utilised. One of the tools that students view as the most helpful is feedback, however, even though it has its benefits, the study emphasises the importance of acknowledging that feedback is a form of grading that similarly to the traditional grading can be misinterpreted. Moreover, the study overviews the variations across and within the students in their perceptions of the fairness in grading additionally revealing a noticeable impact on the psychological well-being of the students. Various aspects of grading are researched through the prism of different researches throughout the time as well as the questionnaire responses, that has been used as the data collection method for this thesis.
Keywords: grading, grade, evaluation, assessment, subjectivity in grading, variation in perception, fairness, feedback, standards-based grading, motivation.